Magnetic Resonance Imaging Texture Analysis in the Detection of Metastatic Lymph Nodes in Patients with Nasopharyngeal Carcinoma - Mehmet Sedat Durmaz; Abdussamet Batur; Abidin Kılınçer; Halil Özer; Nurullah Özdemir (Genel Tıp Dergisi, 2023)
Abstract